Peranan Agro-Ekowisata Terhadap Tingkat Pendapatan Masyarakat (Suatu kasus Agro-Ekowisata Kampung Ciherang Desa Cijambu Kecamatan Tanjungsari, Kabupaten Sumedang Jawa Barat) - Ana Yohana; M Zaenal Irawan (Paspalum: Jurnal Ilmiah Pertanian, 2023)
This study aims to determine the role of agro-ecotourism on people's income levels, carried out in Ciherang village tourism in Cijambu Village, Tanjungsari District, Sumedang Regency using primary and secondary data. Sampling in this study was conducted by survey method with 30 respondents. The variables measured in this study were community work before and after the development of Kampung Ciherang tourism and community income before and after the development of Kampung Ciherang tourism. The analysis technique used the paired t test. The results of the study showed that there were positive changes to the socio-economic community, both in terms of employment and income, which increased after the development of Kampung Ciherang tourism.